COMMUNITY EMPOWERMENT THROUGH SKILLS TRAINING IN MAKING HIGH-VALUE CULINARY PRODUCTS IN SETILING VILLAGE, CENTRAL LOMBOK - Galih Mulya Subastyan; Supratman Supratman; Sari Kartikaningrum; Yayang Erry Wulandari; Tama Krisnahadi (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2026)
ABSTRACT Strengthening rural community economies depends not only on the availability of local resources but also on the capacity of community members to transform these resources into value-added and competitive products. This remains a challenge in Setiling Village, Central Lombok Regency, where existing human resource potential has not been fully supported by adequate food-processing skills, sanitation awareness, and business management capabilities. In response to this condition, this community service program was designed to enhance community capacity through culinary entrepreneurship training that integrates production techniques, food safety practices, cost management, packaging development, and marketing strategies. The program was implemented using a Participatory Action Research (PAR) approach involving housewives and village youth in a series of activities, including needs assessment, practical food-processing training, food hygiene and sanitation assistance, cost-of-goods-sold calculation, packaging improvement, and the utilization of digital media for promotion. The program outcomes indicated improvements in participants’ knowledge and skills in producing culinary products that were more attractive, hygienic, and commercially valuable. Participants also gained a better understanding of business management, product pricing, and the use of pre-order systems and digital media as marketing tools. In addition to enhancing participants’ confidence to engage in entrepreneurial activities, the program demonstrated that integrating technical skills with business competencies can serve as an effective strategy for strengthening community economic capacity and supporting more sustainable rural economic development. ABSTRAK Upaya penguatan ekonomi masyarakat pedesaan tidak hanya ditentukan oleh ketersediaan sumber daya lokal, tetapi juga oleh kemampuan masyarakat dalam mengolah potensi tersebut menjadi produk yang memiliki nilai tambah dan daya saing. Kondisi ini masih menjadi tantangan di Desa Setiling, Kabupaten Lombok Tengah, di mana potensi sumber daya manusia yang tersedia belum sepenuhnya didukung oleh keterampilan pengolahan pangan, pemahaman sanitasi, maupun kemampuan pengelolaan usaha. Berangkat dari kondisi tersebut, kegiatan pengabdian ini dirancang sebagai sarana penguatan kapasitas masyarakat melalui pelatihan kewirausahaan kuliner yang memadukan aspek produksi, keamanan pangan, manajemen biaya, pengemasan, dan pemasaran. Kegiatan dilaksanakan dengan pendekatan Participatory Action Research (PAR) yang melibatkan ibu rumah tangga dan pemuda desa dalam proses identifikasi kebutuhan, pelatihan praktik pengolahan produk, pendampingan higiene dan sanitasi pangan, perhitungan harga pokok produksi, pengembangan kemasan, serta pemanfaatan media digital untuk promosi. Hasil kegiatan menunjukkan adanya peningkatan pengetahuan dan keterampilan peserta dalam menghasilkan produk kuliner yang lebih menarik, higienis, dan bernilai jual. Peserta juga memperoleh pemahaman yang lebih baik mengenai pengelolaan usaha, penentuan harga produk, serta pemanfaatan sistem pre-order dan media digital sebagai sarana pemasaran. Selain meningkatkan kepercayaan diri untuk berwirausaha, program ini memperlihatkan bahwa integrasi keterampilan teknis dan kompetensi bisnis dapat menjadi strategi yang efektif dalam memperkuat kapasitas ekonomi masyarakat serta mendukung pengembangan ekonomi desa yang lebih berkelanjutan.